Benefit, recurrence pattern, and toxicity to adjuvant anti-PD-1 monotherapy varies by ethnicity and melanoma subtype: An international multicenter cohort studyCapsule Summary - Xue Bai, MD; Aleigha R. Lawless, BS; Juliane A. Czapla, MS; Stefanie C. Gerstberger, MD, PhD; Benjamin C. Park, MD; Seungyeon Jung, BA; Rebecca Johnson, MN; Naoya Yamazaki, MD, PhD; Dai Ogata, MD, PhD; Yoshiyasu Umeda, MD; Caili Li, MB; Jun Guo, MD, PhD; et al. (Elsevier, 2024)
Background: Anti-Program-Death-1 (PD-1) is a standard adjuvant therapy for patients with resected melanoma. We hypothesized that there are discrepancies in survival, recurrence pattern and toxicity to adjuvant PD-1 between different ethnicities and melanoma subtypes. Objective: We performed a multicenter cohort study incorporating 6 independent institutions in Australia, China, Japan, and the United States. The primary outcomes were recurrence free survival (RFS) and overall survival (OS). Secondary outcomes were disease recurrence patterns and toxicities. Results: In total 534 patients were included. East-Asian/Hispanic/African reported significantly poorer RFS/OS. Nonacral cutaneous or melanoma of unknown primary reported the best RFS/OS, followed by acral, and mucosal was the poorest. Within the nonacral cutaneous or melanoma of unknown primary subtypes, East-Asian/Hispanic/African reported significantly poorer RFS/OS than Caucasian. In the multivariate analysis incorporating ethnicity/melanoma-subtype/age/sex/stage/lactate dehydrogenase/BRAF (v-Raf murine sarcoma viral oncogene homolog B)-mutation/adjuvant radiotherapy, East-Asian/Hispanic/African had independently significantly poorer outcomes (RFS: HR, 1.71; 95% CI, 1.19-2.44 and OS: HR, 2.34; 95% CI, 1.39-3.95), as was mucosal subtype (RFS: HR, 3.25; 95% CI, 2.04-5.17 and OS: HR, 3.20; 95% CI, 1.68-6.08). Mucosal melanoma was an independent risk factor for distant metastasis, especially liver metastasis. East-Asian/Hispanic/African had significantly lower incidence of gastrointestinal/musculoskeletal/respiratory/other-rare-type-toxicities; but higher incidences of liver toxicities. Limitations: A retrospective study. Conclusions: Ethnicity and melanoma subtype are associated with survival and recurrence pattern in melanoma patients treated with adjuvant anti-PD-1. Toxicity profile differs by ethnicity and may require a precision toxicity surveillance strategy.